Atypical Guillain–Barre syndrome with T6 sensory level - Osamah Al‐Ameen; Mohanad Faisal; Salma Mustafa; Mohammed Alhatou (Clinical Case Reports, 2022)
Abstract Guillain–Barré syndrome is an acute immune‐mediated demyelinating disease. Typical features include progressive ascending lower extremity weakness and areflexia. Several variants have been described that can make the diagnosis challenging. Here, we report a case of GBS presenting with progressive lower limb weakness and T6 sensory level.